2009
DOI: 10.1093/gerona/gln050
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Hypertrophy Following Resistance Training Is Accompanied by a Fiber Type-Specific Increase in Satellite Cell Content in Elderly Men

Abstract: We determined muscle fiber type-specific hypertrophy and changes in satellite cell (SC) content following a 12-week resistance training program in 13 healthy, elderly men (72 +/- 2 years). Leg strength and body composition (dual-energy X-ray absorptiometry and computed tomography) were assessed, and muscle biopsy samples were collected. Leg strength increased 25%-30% after training (p < .001). Leg lean mass and quadriceps cross-sectional area increased 6%-9% (p < .001). At baseline, mean fiber area and SC cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
307
10
15

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(373 citation statements)
references
References 40 publications
24
307
10
15
Order By: Relevance
“…These data suggest that the loss of type II fiber SC content may be important in the etiology of type II fiber atrophy in older adults. Furthermore, chronic exercise training may reverse some of the age-related alterations in gene expression and restore the type II SC content (40,58); however, the mechanisms remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that the loss of type II fiber SC content may be important in the etiology of type II fiber atrophy in older adults. Furthermore, chronic exercise training may reverse some of the age-related alterations in gene expression and restore the type II SC content (40,58); however, the mechanisms remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…NCAM, Pax7), or through electron microscopy. The results of a number of training studies suggest that in the long term, satellite cell number can be successfully increased in older individuals (Roth et al 2001, Mackey et al 2007, Verdijk et al 2009, Verney et al 2008 with no reported age related impairments (Roth et al 2001, Verdijk et al 2009). Furthermore, in an analysis of young and old male and female subjects who underwent sixteen weeks of strength training exercise (Petrella et al 2006) and who were subsequently clustered into cohorts of responders and nonresponders (Petrella et al 2009), the ability of responders to increase myofibre crosssectional area was correlated with increased satellite cell and myonuclear number, independently of age.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…As células satélites são células mononucleares, quiescentes e caracterizadas por estarem localizadas entre o sarcolema e a lamina basal apresentando a capacidade de proliferação e diferenciação estando intimamente ligadas ao processo de hipertrofia muscular (MUIR, KANJI e ALLBROOK, 1965;HAWKE e GARRY, 2001;PETRELLA et al, 2008;BELLAMY et al, 2014;BLAAUW e REGGIANI, 2014). Tanto a idade como o nível de treinamento parecem ser capazes de modular as respostas dos genes e das proteínas envolvidas no processo de ativação das células satélites, bem como a quantidade das mesmas que são fundidas às células musculares esqueléticas PETRELLA et al, 2006;RAUE et al, 2006;VERDIJK et al, 2009). De maneira oposta, o fator miogênico 6 (myf 6) apresentou aumentos na sua quantidade total, porém sem aumento de expressão gênica.…”
Section: Revisão Bibliográficaunclassified
“…A área de secção transversa da fibra pode ser analisada por reação histoquímica pela enzima ATPase bem como por imunofluorescência, sendo os dois métodos bastante encontrados na literatura em questão (CAMPOS et al, 2002;KADI et al, 2004a;KADI et al, 2004b;LINDSTROM e THORNELL, 2009;VERDIJK et al, 2009). A análise da área das fibras permite termos uma visão bastante local do que está ocorrendo com os diferentes tipos de fibra, proporcionando um entendimento mais preciso e específico com relação ao comportamento das mesmas frente ao envelhecimento ou frente a diferentes intervenções de treinamento físico (CAMPOS et al, 2002;PETRELLA et al, 2006;VERDIJK et al, 2009;NILWIK et al, 2013).…”
Section: áRea De Secção Transversa Das Fibras Musculares (Astf)unclassified
See 1 more Smart Citation